Managing Weed in Maize in Temperate Conditions of Kashmir Valley - Bahar, Fayaz Ahmed (Indian Farming, 2015)
For obtaining higher productivity in maize, it has to be protected from infestation by various weeds that grow side by side with it. Weed management is one of the important factors in the maize improvement programme as otherwise it has to compete with the weeds for nutrition, space, light, moisture, etc.